Business process model and notation Third International Workshop, BPMN 2011, Lucerne, Switzerland, November 21-22, 2011. Proceedings - Dijkman, Remco; Hofstetter, Jörg; Koehler, Jana (Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the third workshop on Business Process Model and Notation, BPMN 2011, held in Lucerne, Switzerland, in November 2011. The 8 research papers presented were carefully reviewed and selected from 20 submissions. In addition, 10 short papers are included. The workshop applied a thorough reviewing process, during which each paper was reviewed by three Program Committee members. The BPMN workshop series provides a forum for academics and practitioners who share an interest in business process modeling using the business process modeling notation, which is seen by many as the de facto standard for business process modeling. This year, the workshop lasted two days and consisted of both a scientific and a practitioner event.